Peran Teknik Ego Strength dalam Meningkatkan Kemampuan Regulasi Emosi Anak Fatherless - Imaniar, Anggun; Salsabila, Kultsum; Lathifah, Naia; Ratnadillah, Yekti; Afridah, Mumtaz (Universitas Pahlawan Tuanku Tambusai, 2025)
The family is the first place a child lives, which plays an important role in his emotional development, especially the ability to control his emotions. Children's psychological development is influenced by parental figures, the role of mother and father. Fathers in the family play a role in children's development to recognize, control and express emotions adaptively. However, for children who grow up without a father figure or are orphaned, whether due to divorce, death, or emotional absence, it is often found that children end up having difficulty managing emotions, which can have an impact on self-confidence, social interactions, and even the emergence of psychological disorders. The purpose of this research is to see how the Ego Strength technique helps children who do not have a father's role to control their emotions. This research was conducted qualitatively using a descriptive approach. To collect data, semi-structured interviews and observations were conducted on individuals who did not have a father figure. The research results show that the Ego Strength technique is effective in strengthening personality aspects and regulating the emotions of children who do not have a father. Study subjects showed significant improvements in their ability to recognize emotions, manage stress, and communicate their feelings in a more flexible way. Fatherless children can develop self-awareness, build psychological resilience, and overcome the emotional challenges they face.